THE EFFECT OF WORKLOAD AND WORK INCENTIVES ON EMPLOYEE JOB SATISFACTION AT PT TIRTA SUKSES PERKASA IN JEMBER REGENCY - Agussalim Andriansyah; Listya Paramita; Andiani, Lidia (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
The purpose of this study was to determine the effect of workload on employee job satisfaction, the effect of work incentives on employee job satisfaction, and the effect of workload and work incentives simultaneously on employee job satisfaction at PT Tirta Sukses Perkasa in Jember Regency. This research uses descriptive quantitative research. In this study, researchers used data collection techniques by distributing questionnaires to employees of PT Tirta Sukses Perkasa in Jember Regency. Based on the results of the study, researchers found that workload has a negative and significant effect on employee job satisfaction, then work incentives have a positive and significant effect on employee job satisfaction, and the effect of workload and work incentives simultaneously and individually has a significant effect on employee job satisfaction. The contribution of researchers in this study is expected to help in providing literature development on the relationship between workload, work incentives, and job satisfaction, and is expected to help companies to manage workload proportionally and effectively which can reduce the negative impact on job satisfaction and increase productivity